Archétypes du corps cinématographique du narcotrafiquant mexicain - Magali Kabous (Caravelle)
This paper explores three Mexican fiction feature films internationally released in 2011: Miss Bala, Days of grace and El Infierno. The movies propose three different criminality’s representations related to drug trafficking. Therefore, we try to draw various archetypes of the drug dealer’s body in films. How do filmmakers depict their character, their physical appearance and metamorphosis and their integration into a group? To what extent are these accusing portraits? Do they contribute to maintain the attraction towards this figure, fictional as well as real?